ANALYSIS OF THE CAUSES OF ALLERGIC DISEASES IN THE HUMAN BODY AND THE EFFECTS OF DRUGS USED AGAINST THEM - Makhmudov Otabek Shukhratjon ugli (Scholar Express Journals, 2023)
This article contains information about the causes of allergic diseases in the human body
Keywords: Allergy; immunobiological; allergen